Surface hardness effects on biomechanics foot response during running - Noor Arifah Azwani Abdul Yamin (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2017)
The principle aim of this research is to investigate the effect of surface hardness on the biomechanical response of foot during running with different shod conditions that may lead to injury. The task was divided into three specific objectives as follows ; to determine the effect running surface hardness on joint rotation of multi-segmentfoot kinematics ; to analyze the influence of running surface hardness on temporal parameter and kinetic responses (i.e. plantar fascia strain and ground reaction force) ; to determine the correlation of kinematic and kinetic responses during running on different surface hardness in different shod conditions (i.e. barefoot (BF) heeled running shoe (HS) and minimally running shoe (MS)) ; to understand etiology of plantar fasciitis which one of common injury risk to runners.